PENGARUH METODE GUIDED DISCOVERY TERHADAP KEMAMPUAN KONEKSI MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VIII SMP NEGERI 58 MERANGIN - Destia Melinda Astuti; Yohanes; sukur (Hiradika | Hira Institute, 2026)
The low mathematical connection skills motivated this research. Students have not yet achieved mastery of the mathematical connection skills indicators. The purpose of this research is to describe mathematical connection skills, reviewed from the perspective of independent learning taught using the guided discovery learning method, which is better than conventional learning for eighth-grade students at SMP Negeri 58 Merangin. This study used quantitative techniques and an experimental design with a 2x3 factorial pattern with a population of VIII grade students consisting of 2 classes. The sampling technique used simple random sampling, while the data collection method used essay questions and a learning independence questionnaire. According to the data analysis, it shows that hypothesis 1t_count>t_table or 1.8607>1.679 and hypothesis 3 t_count>t_table or 2.283>1.679 then it is concluded that the mathematical connection ability using the guided discovery learning method is better than conventional learning of students as a whole or moderate learning independence, hypothesis 2 t_count<t_table or -0.128<2.015 and hypothesis 4 t_count<t_table or 1.591<1.895 which means the mathematical connection ability using the guided discovery learning method is better than conventional learning of students who have high and low learning independence. Furthermore, hypothesis 5 obtained F_count<F_table or 0.691<3.191 with the conclusion that there is no interaction between the guided discovery method in terms of learning independence in influencing students'